2008
DOI: 10.1016/j.acra.2008.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Human Pulmonary Imaging and Spectroscopy with Hyperpolarized 129Xe at 0.2T

Abstract: Hyperpolarized (129)Xe human imaging and spectroscopy are very promising methods to provide functional information about the lung.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
149
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(150 citation statements)
references
References 19 publications
(46 reference statements)
0
149
0
Order By: Relevance
“…While in conventional proton MRI the signal-to-noise ratio (SNR) increases with higher B 0 field strength, the influence of B 0 on imaging of hyperpolarized species is less obvious (1), and imaging at low field strengths becomes feasible and possibly preferable due to longer transverse relaxation times (2)(3)(4)(5).…”
mentioning
confidence: 99%
“…While in conventional proton MRI the signal-to-noise ratio (SNR) increases with higher B 0 field strength, the influence of B 0 on imaging of hyperpolarized species is less obvious (1), and imaging at low field strengths becomes feasible and possibly preferable due to longer transverse relaxation times (2)(3)(4)(5).…”
mentioning
confidence: 99%
“…This phenomenon has been observed previously at field strengths of 0.2 T (6) in humans and at 4.7 T (35) in guinea pigs. Patz et al (6) hypothesized that this enhanced spin-spin relaxation is due to slow exchange of the 129 Xe with one or more of the dissolved phases. This hypothesis is supported by the observation of multiple spin-spin relaxation components in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Although most previous studies have employed 3 He due to its higher signal-to-noise ratio (SNR), 3 He has a very low natural abundance, making it a poor candidate for widespread clinical use. Conversely, 129 Xe gas has the advantage over 3 He of being more abundant in the atmosphere and therefore relatively inexpensive compared with 3 He (6). 129 Xe is also highly soluble in blood and displays an exquisite sensitivity to its local environment through a broad range of chemical shift and relaxation effects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that several physiological quantities related to these processes were globally evaluated from measurements of alveolar gas uptake dynamics using CSSR in animals 30,[42][43][44][45] and humans. 39,46,47 Whole-lung spectroscopy, however, limits the assessments to be accepted as global measures without any information about the spatial distribution in the lung. An extension of spectroscopybased methods to imaging-based methods is an important step toward identifying a region with impaired function with higher sensitivity and evaluation of its variation in the whole lung.…”
Section: Dissolved-phase 129 Xe Mrimentioning
confidence: 99%